Analisis Produktivitas pada PT XYZ Menggunakan Metode Objective Matrix - Difa Afgan Al Hafiz; Risma Fitriani; Wahyudin Wahyudin (Fakultas Teknik, 2023)
PT XYZ is trying to increase its productivity because some of this time it is still considered ineffective. Productivity measurements based on fragrance output and the inputs used are the use of raw materials, the amount of labor, machine hours, and electrical energy used. Based on these problems, Objective Matrix (OMAX) is used as a measurement of productivity on the production line. The data used is data from January 2022 to May 2022. The results of the performance indicators that can be achieved by the company during the period January 2022 to May 2022 experienced productivity fluctuations. The highest productivity increase happened in the April 2022 period, at 146.67, while the lowest decline in productivity occurred in the February 2022 period, at -13.33. The factors that need to be improved are the number of employees, the machine's working hours, and the amount of electrical energy utilized.